Increasing access to clean cooking in the Philippines challenges and prospects. (Economics working papers.)
In Asia and the Pacific, 1.8 billion people still rely on traditional cooking methods using fires and solid fuels. The wider uptake of cleaner cooking solutions is vital for achieving the Sustainable Development Goal 7 objective of universal access to modern, affordable, reliable, and sustainable modern energy. It is also important for the environment and human health. Based on a study of household cooking practices in the Philippines, this publication provides insights and recommendations to encourage clean cooking in the country. The findings identify policy, information, technology, and financing gaps that must be addressed to boost the development and market expansion of clean cooking technologies.